Employment protection reforms and labour market outcomes in the aftermath of the recession: Evidence from Croatia (Public Sector Economics - submission site, 2020)
This paper examines the effects of employment protection legislation (EPL) reforms on employment outcomes in Croatia, testing the available theoretical predictions of partial labour market reforms from the literature. Using Labour Force Survey (LFS) data in the period 2007-2017 and applying the event study method in combination with probit regressions, the main results suggest that EPL reforms from 2013 and 2014 induced a rise in temporary employment, while the effects on overall employment are clearly visible only in the case of the second reform. Moreover, probit regression estimations show that specific groups of the population – females, youths, foreigners, the low-skilled and singles from rural areas – have a higher probability of ending up with temporary contracts, suggesting there is a segmentation on the Croatian labour market.